COMPARATIVE DRIVE CYCLE FUEL ECONOMY OF IN-USE PUBLIC UTILITY JEEPNEYS USING 2% AND 5% CME-DIESEL BLENDS - Quiros, Edwin; Vergel, Karl (Philippine Engineering Journal; Vol 36 No 1 (2015), 2016)
This study presents the results of drive cycle tests conducted on in-use public utility jeepneys running on 2% (B2), and 5% (B5) by volume Coconut Methyl Ester (CME)-Diesel blends. The tests measured fuel consumption of sample jeepney units on a chassis dynamometer driven following the European ECE1504 Drive Cycle fueled with B2 and B5 CME-Diesel blends. These tests were part of an overall study examining the effects of B2 and B5 blends on the economic operation and fuel economy, measured on-road and in the laboratory, of jeepneys conducted by the UP National Center for Transportation Studies (UP NCTS) and UP Vehicle Research and Testing Laboratory (VRTL) for the Philippine Coconut Authority (PCA). Data from the study will be used as one of the inputs, among others such as economic, logistics, and fuel quality issues, to deliberations to decide for the introduction of 5% CME-Diesel blend in commercial diesel fuel. The drive cycle tests of seven (7) jeepney units range from about 0.5% to 11% specific fuel consumption (gm/km) improvement for B5 relative to B2 for an overall average SFC improvement of 4.6%. The change in mileage for B5 relative to B2 ranged from -2.40 to +11.91 percent for an overall average of around 3.0%. The mileage results were affected by the observed relative density of B5 with respect to B2 – a less B5 density than B2 adversely affects B5 mileage versus B2. “Mixed” mileage results were observed. The amount of fuel economy change when using B5 compared to B2 in jeepneys is thought to also depend on in-use engine conditions and drivetrain configuration. While the observed overall better fuel economy of B5 relative to B2 tends to favor a shift to B5 diesel blend implementation, the authors recommend further detailed studies on CME-diesel blend effects on engine/vehicle performance and emissions for a more sound technical basis for policy decisions.   Key words : CME, biodiesel, jeepney, fuel economy, drive cycle